Clinical features and outcome of patients with severe lower respiratory tract infection admitted to a Paediatric Intensive Care Unit in the Western Cape, South Africa - Hutton, Hayley (Department of Paediatrics and Child Health, 2017)
Objective: Acute lower respiratory tract infection (ALRTI) remains an important cause of childhood morbidity and mortality in low and middle income countries (LMIC). This study aims to describe the clinical features of children admitted to a Pediatric Intensive Care Unit (PICU) with severe ALRTI and to investigate risk factors, clinical course and in-hospital outcome. Design: Retrospective cohort study Setting: Red Cross War Memorial Children's Hospital, Cape Town, South Africa Patients: 265 children (0-12years) admitted to the PICU during 2012 with a primary diagnosis of ALRTI. Intervention: None. Measurements and main results: 265 patients [median (interquartile range, IQR) age 4 months (2-12months)] were admitted with ALRTI, 157(59.3%) were male. Co-morbid disease was present in 102(38.5%) including cardiac disease in 42(15.9%) or tuberculosis in 7(6.4%) . While only 27(10.2%) were HIV infected, 87(32.8%) children were HIV exposed. The in-hospital mortality was 34(12.8%); 24(9.1%) died in PICU and a further 10 in the medical wards following discharge from PICU. The median duration of ICU and hospital stay was 4.0 days (2.0-8.0) and 12.5 days (7.9-28.0) respectively. Most [192 (72.5%)] children required invasive ventilatory support, while 42 (15.8%) patients required cardiac inotropic support. Risk factors for mortality included severe malnutrition (Odds ratio (OR) 8.25; 95% CI 1.47- 46.21); informal housing without access to piped water and/or electricity (OR11.87; CI 1.89- 20.81); or need for inotropic support (OR 44.35; CI 8.20-239.92). HIV exposure or infection was associated with a significantly longer duration of hospital stay (p=0.002). Conclusion: Severe ALRTI occurs predominantly in young infants and is associated with a high mortality. Several sociodemographic risk factors impact on the risk of severe disease and poorer outcome.